2001
DOI: 10.1074/jbc.m103306200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Regulation in Human Versus Rodent Hepatocytes by Peroxisome Proliferator-activated Receptor (PPAR) α

Abstract: We compared the ability of rat and human hepatocytes to respond to fenofibric acid and a novel potent phenylacetic acid peroxisome proliferator-activated receptor (PPAR) ␣ agonist (compound 1). Fatty acyl-CoA oxidase (FACO) activity and mRNA were increased after treatment with either fenofibric acid or compound 1 in rat hepatocytes. In addition, apolipoprotein CIII mRNA was decreased by both fenofibric acid and compound 1 in rat hepatocytes. Both agonists decreased apolipoprotein CIII mRNA in human hepatocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…[17][18][19] Our results suggest that LFO suppresses abdominal fat accumulation by regulation of rate-limiting enzyme activities related to fatty acid synthesis and oxidation in the liver.…”
Section: Investigation Of the Anti-obesity Action Of Licorice Flavonomentioning
confidence: 66%
“…[17][18][19] Our results suggest that LFO suppresses abdominal fat accumulation by regulation of rate-limiting enzyme activities related to fatty acid synthesis and oxidation in the liver.…”
Section: Investigation Of the Anti-obesity Action Of Licorice Flavonomentioning
confidence: 66%
“…It has been shown that activation of PPAR␣ leads to transcriptional up-regulation of the CYP4A genes, which are also constituents of the microsomal biotransformation system in both proliferating and nonproliferating species (Lawrence et al, 2001;Cheon et al, 2005). It has further been shown that some UGT isoforms (UGT1A9, UGT2B4) are PPAR␣ target genes (Barbier et al, 2003a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Several genes are known that are targets of PPAR␣ in mice but not in humans (30,31). To investigate whether expression of FIAF is under control of PPAR␣ in other species, rat hepatoma FAO cells were treated with the PPAR␣ agonist Wy14643 (Fig.…”
Section: Fiaf Expression Is Regulated By All Three Ppars-previousmentioning
confidence: 99%